ADR a comparative study in common law jurisdiction – How does North America compare with the rest of the world - Bailey, Richard (2020)
In this document, the author will provide a general description of ADR in common law jurisdictions, but with a particular emphasis on how ADR is practiced in North America (for this document, it refers to the countries of EE. USA and Canada). Also, will focus on the way ADR is implemented in North America and compare this with the way ADR is implemented in England the largest common law jurisdictions outside of North America. In that sense, as the reader may know, most legal jurisdictions in North America are common law.